If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -16 + n = -15 Solving -16 + n = -15 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + n = -15 + 16 Combine like terms: -16 + 16 = 0 0 + n = -15 + 16 n = -15 + 16 Combine like terms: -15 + 16 = 1 n = 1 Simplifying n = 1
| 4444x-2200=44(101x-50) | | (5x+9)+6=-1 | | 9.x=3.5 | | -2(x+6)=-2x+5 | | -8=-6x+(5x-3) | | 4(3x+3)=17x+8-5x+4 | | Y/4=-7/1 | | 8-n=-10+6n-4n | | 2/3y+y=35 | | 25x^2+70xy+49y^2=0 | | 2/3x+8=24 | | 7x-6=-38+3x | | 3x^0/x^2 | | 5(x+3)=1+5x | | z=q-qab | | -8(-8)-8= | | x^2-12x=60 | | T-1/4=-3/4 | | q=p-q/2 | | z(z+2)=63 | | 9/5m=1/5 | | (8/(3x+1))-(27x/(3x-1))=-9 | | 9=6(-b+7)+7(b-5) | | k^3/2k^2 | | -2x+7-5x=-70 | | X+x+130=750 | | -5(8v-8)-4(5v+8)=8 | | (-2xy^4(z^2))(-3x^6(y^4)(z^4))= | | 7+x/2=8 | | B=2X+11 | | 2x+4/3=5 | | -12(9x+1)=-144 |